Pengaruh Related Party Transaction, Multinationaly,Thin Capitalization terhadap Agresivitas Pajak pada Perusahaan Manufaktur - Cyndi Nurariza (Journal of Business and Economics (JBE) UPI YPTK, 2019)
The purpose of this study was to examine the effect of related party transactions, multinationality, thin capitalization on tax aggressiveness with firm size as a moderating variable. The object of the research is manufacturing companies listed on the Indonesia Stock Exchange for the period 2016 to 2020. The population used in this study is 193 companies. The type of data used in this research is quantitative data using purporsive sampling method. The sample in this study were 8 companies. The results of this study indicate that (1) Related Party Transaction partially has no significant effect on Tax Aggressiveness (2) Multinationality partially has a significant effect on Tax Aggressiveness (3) Thin Capitalization partially has a significant effect on Tax Aggressiveness (4) Related Party Transaction has a significant effect on Tax Aggressiveness with Company Size as a moderating variable (5) Multinationality has no significant effect on Tax Aggressiveness with Company Size as a moderating variable (6) Thin Capitalization has a significant effect on Tax Aggressiveness with Company Size as a moderating variable